EMS Induced Cytomictic Variability in Safflower (Carthamus tinctorius L.) - Srivastava, P.; Kumar, G. (Цитология и генетика, 2011)
Seeds of safflower (Carthamus tinctorius L.) were subjected to three treatment durations (3h, 5h and 7h) of 0.5 % Ethyl Methane Sulphonate (EMS). Microsporogenesis was carried out in the control as well as in the treated materials. EMS treated plants showed interesting feature of partial inter-meiocyte chromatin migration through channel formation, beak formation or direct cell fusion. Another interesting feature noticed during the study was the fusion among tetrads due to wall dissolution. The phenomenon of cytomixis was recorded at nearly all the stages of microsporogenesis connecting from a few to several meiocytes. Other abnormalities such as laggards, precocious movement, bridge and non disjunction of chromosomes were also recorded but in very low frequencies. The phenomenon of cytomixis increased along with the increase in treatment duration of EMS. Cells with these types of cytomictic disturbances may probably result in uneven formation of gametes or zygote, heterogenous sized pollen grains or even loss of fertility in future.